Analysis of PDDikti Website User Satisfaction Using Webqual - Ony Ichsandrya; Erma Suryani (Institut Teknologi Sepuluh Nopember, 2020)
Based on Presidential Instruction of the Republic of Indonesia Number 3 of 2003 concerning National Policies and Strategies for E-Government Development, it is hoped that the government can provide services that are efficient, effective, transparent and accountable. One application is through the use of websites or websites in all government and non-government institutions, the Ministry of Research, Technology and Higher Education as one of the government institutions through its work unit, PUSDATIN, which provides services to stakeholders through the PDDikti website as an application of the development of E-Government initiated by the government. This research was conducted to identify PDDikti website service user satisfaction, namely by measuring user satisfaction using the modified Webqual 4.0 method and seeing the extent to which the intensity of use variables moderates the quality of service on PDDikti website service user satisfaction. The population and sample in this study are operators of Private Universities in East Java under the auspices of LLDIKTI Region VII, the statistical analysis used in this study is the statistical analysis of Partial Least Square (PLS), to see the extent of the influence of each variable used in this research. The final results expected from this study are, looking at the effect of service quality on user satisfaction, as well as looking at the moderating effect posed (positive / negative) by the Intensity Usage variable. This study resulted in the findings that the Variable Usual Quality, Information Quality, Services Interaction, and Visual Quality had a significant effect with a P-Value below 0.05, as well as a positive moderating effect of the Usage Intensity Variable with a P value of <0.01.